Description of cryptic taxa within the Alpheus bouvieri A. Milne-Edwards, 1878 and A. hebes Kim and Abele, 1988 species complexes (Crustacea: Decapoda: Alpheidae) - Anker, Arthur; Hurt, Carla; Knowlton, Nancy (Zootaxa, 2009)
Alpheus bouvieri A. Milne-Edwards, 1878 and A. hebes Kim and Abele, 1988 are reviewed based on morphological and genetic data. Alpheus bouvieri, previously believed to be distributed in the eastern Pacific and Atlantic, is restricted to the Atlantic populations; the eastern Pacific populations (A. bouvieri sensu Kim and Abele 1988) are assigned to A. javieri n. sp. A second new species, A. agilis n. sp., closely related to the eastern Pacific A. hebes, is described based on recently collected specimens from the eastern Atlantic (São Tomé, Cape Verde) and western Atlantic (Atol das Rocas off northeastern Brazil). The absence of A. agilis n. sp. (or any other representative of the A. hebes clade) in the Caribbean Sea is likely due to a relatively recent ( 1–2 my) extinction. Genetic data (COI sequences) indicates that A. bouvieri and A. javieri n. sp., and A. hebes and A. agilis n. sp. diverged approximately 6 and 7.5 mya, respectively, i.e., around 3 my before the final closure of the Isthmus of Panama.